Biologic Treatment of 4 HIV-Positive Patients: A Case Series and Literature Review. Issue 1 (January 2021) - Myers, Bridget; Thibodeaux, Quinn; Reddy, Vidhatha; Chan, Stephanie; Brownstone, Nicholas; Liao, Wilson; Bhutani, Tina
Background: The management of psoriatic disease in HIV-positive patients is challenging. Psoriasis in HIV-positive patients is often severe, progressive, and resistant to first- and second-line therapies, including topical treatments, phototherapy, highly active antiretroviral therapy (HAART), and oral retinoids. Other systemic agents used to treat psoriasis, such as methotrexate and cyclosporine, are immunosuppressants and thus many dermatologists may not feel comfortable prescribing them to HIV-positive patients who are already immunocompromised. Biologic agents, which target specific aspects of overactive immune pathways in psoriasis, have revolutionized the management of moderate-to-severe psoriasis. However, data are limited regarding their safety and efficacy in HIV-positive patients. Objective: Report 4 cases of HIV-positive patients managed on biologic therapy and summarize the cases of psoriasis in HIV-positive patients managed on biologic therapy that have been published in dermatologic literature to date. Methods: We searched PubMed and Embase databases using the terms HIV and psoriasis or HIV and psoriatic arthritis combined with one of the 11 biologics currently approved for treating psoriasis. Results: We identified 48 cases of anti-psoriasis biologic therapy (including adalimumab, infliximab, etanercept, ustekinumab, and guselkumab) in HIV-positive patients and added 4. While data are limited, the evidence available suggests biologic agents are safe and efficacious in moderate-to-severe psoriasis and may even have a favorable effect on CD4 and HIV viral counts when used with concomitant HAART. Conclusion: Further research would be helpful to establish practical guidelines for the use of anti-psoriasis biologic therapy in the HIV population, including that of newer agents.